PERBEDAAN GENDER DALAM PENGUASAAN BAHASA DIPANDANG DARI PERSFEKTIF PSIKOLOGI PENDIDIKAN - Sri Yuliani (Pedagogi: Jurnal Ilmu Pendidikan, 2013)
This article is concerned with the diversity of gender in acquiring language in psychological perfectives. The language and gender are the main factors which the writer tries to expose. The language using for each gender is observed by the psychological perfectives and the data collected by using descriptive literature analysis. The fact showed that the factors of the diversity of language in each gender are contributed by psychological matter from their family background, the superiority, and socio cultural phenomenon.